Underground Water Flow betwen Bloke Plateau and Cerknica Polje and Hydrologic Function of Križna Jama, Slovenia - Kogovšek, Janja; Prelovšek, Mitja; Petrič, Metka (Acta Carsologica, 2008)
Križna jama and Križna jama 2 are of important natural value. They have been known for more than hundred years from speleobiological, paleontological, geomorphological and touristic points of view. In 2007 the establishment of a water treatment plant on Bloke plateau raised important question: can partly cleaned water from the water treatment plant contaminate both caves and decrease their value? To answer this question a tracer test was carried out at the Bloke plateau. It showed general underground water flow from Farovščica ponor at Bloke plateau toward the Šteberščica spring at Cerknica polje. Minority of recovered tracer appeared at Žerovniščica and Izvir v Podložu springs. The tracer was not detected at Studenec v Ložu and Zlatovec springs. Between ponor and springs three karst caves were observed. The highest concentration of tracer was detected in the cave Mrzla jama pri Bločicah and a much smaller concentration in the Križna jama and Križna jama 2. This shows that at middle water level the underground Farovščica stream does not flow directly through Križna jama and Križna jama 2 but near or below them. Since the tracer appeared in both caves only after the precipitation, underground water course can be significantly different at high water level. Tracing test also showed some characteristics of underground water flow through dolomite and characteristics of a composed aquifer with alogenic-autogenic recharge.